ANALISIS BASIS LUAS LAHAN DAN PRODUKSI TANAMAN KAKAO DI GUNUNGKIDUL BERDASARKAN METODE ANALISIS LOCATION QUOTIENT (LQ) - Azizah, Laili Wafiq; Harli, Nurlina (Agros Journal of Agriculture Science, 2024)
Gunungkidul Regency is known to have diverse agricultural potential, including cocoa, which is one of the leading plantation crops in this area. This research aims to determine the production base and area of cocoa plantations in Gunungkidul Regency. The data used in this research includes land area and cocoa production over the last five years, obtained from the Central Statistics Agency (BPS) and related agencies. Location Quotient (LQ) analysis determines the cocoa crop base based on land area and production in Gunungkidul Regency. Based on the results of research on determining land area and production bases, it is known that there are three (3) sub-districts (Ponjong, Karangmojo, Patuk) in the Gunungkidul region whose LQ value is more than one (>1). There are three (3) sub-districts (Nglipar, Playen, Gendangsari) with LQ results of less than one (<1). The research results show that cocoa plants have the potential to continue to be developed in Gunungkidul, with the need to increase production efficiency and more intensive policy support